CONSULTORIA ECONÔMICA ORGANIZACIONAL - Trennepohl, Dilson; Macagnan, Roberto; Kohler, Romualdo; Stofel, Janete; Juliani, Lucelia; Marks, Gabriela; Petry, Débora C.; Zingler, Karine D. (Salão do Conhecimento, 2013)
Resumo